States of the art and practice in the optimum seismic design and analytical response prediction of R/C frame-wall structures - 187341 Aktan, A. E.; Bertero, Vitelmo V.; University of California. College of Engineering. Earthquake Engineering Research Center (Berkeley, Calif. : University of California, 1982)
03